Prospective comparison of magnetic resonance imaging to transient elastography and serum markers for liver fibrosis detection. (7th February 2016) - Dyvorne, Hadrien A.; Jajamovich, Guido H.; Bane, Octavia; Fiel, M. Isabel; Chou, Hsin; Schiano, Thomas D.; Dieterich, Douglas; Babb, James S.; Friedman, Scott L.; Taouli, Bachir
Abstract: Background & Aims: Establishing accurate non‐invasive methods of liver fibrosis quantification remains a major unmet need. Here, we assessed the diagnostic value of a multiparametric magnetic resonance imaging (MRI) protocol including diffusion‐weighted imaging (DWI), dynamic contrast‐enhanced (DCE)‐MRI and magnetic resonance elastography (MRE) in comparison with transient elastography (TE) and blood tests [including ELF (Enhanced Liver Fibrosis) and APRI] for liver fibrosis detection. Methods: In this single centre cross‐sectional study, we prospectively enrolled 60 subjects with liver disease who underwent multiparametric MRI (DWI, DCE‐MRI and MRE), TE and blood tests. Correlation was assessed between non‐invasive modalities and histopathologic findings including stage, grade and collagen content, while accounting for covariates such as age, sex, BMI, HCV status and MRI‐derived fat and iron content. ROC curve analysis evaluated the performance of each technique for detection of moderate‐to‐advanced liver fibrosis (F2–F4) and advanced fibrosis (F3–F4). Results: Magnetic resonance elastography provided the strongest correlation with fibrosis stage ( r = 0.66, P < 0.001), inflammation grade ( r = 0.52, P < 0.001) and collagen content ( r = 0.53, P = 0.036). For detection of moderate‐to‐advanced fibrosis (F2–F4), AUCs were 0.78, 0.82, 0.72, 0.79, 0.71 for MRE, TE, DCE‐MRI, DWI and APRI, respectively. For detection of advanced fibrosis (F3–F4), AUCs were 0.94, 0.77, 0.79, 0.79 and 0.70, respectively. Conclusions: Magnetic resonance elastography provides the highest correlation with histopathologic markers and yields high diagnostic performance for detection of advanced liver fibrosis and cirrhosis, compared to DWI, DCE‐MRI, TE and serum markers. Abstract : See Editorial on Page631